2004
DOI: 10.1104/pp.103.038315
|View full text |Cite
|
Sign up to set email alerts
|

Differential Timing of Spider Mite-Induced Direct and Indirect Defenses in Tomato Plants

Abstract: Through a combined metabolomics and transcriptomics approach we analyzed the events that took place during the first 5 d of infesting intact tomato (Lycopersicon esculentum) plants with spider mites (Tetranychus urticae). Although the spider mites had caused little visible damage to the leaves after 1 d, they had already induced direct defense responses. For example, proteinase inhibitor activity had doubled and the transcription of genes involved in jasmonate-, salicylate-, and ethylene-regulated defenses had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
374
3
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 336 publications
(415 citation statements)
references
References 59 publications
27
374
3
4
Order By: Relevance
“…4b). Induction of LeGGPS1 by spider mite-herbivory conWrms the microarray results from Kant et al (2004). Treatment of intact plants with JA induced the expression of LeGGPS1 (Fig.…”
Section: Leggps1 Is Not a Typical Ja-or Sa-responsive Genesupporting
confidence: 80%
See 3 more Smart Citations
“…4b). Induction of LeGGPS1 by spider mite-herbivory conWrms the microarray results from Kant et al (2004). Treatment of intact plants with JA induced the expression of LeGGPS1 (Fig.…”
Section: Leggps1 Is Not a Typical Ja-or Sa-responsive Genesupporting
confidence: 80%
“…Thus we have identiWed two novel regulatory steps in the biosynthesis of TMTT in tomato. Kant et al (2004) have previously shown that DOXPS, the limiting step in plastidial IPP and DMAPP biosynthesis (Botella-Pavia et al 2004), was upregulated in tomato by spider mite-feeding ). This brings on the question why there are multiple steps in the biosynthesis of TMTT that are regulated.…”
Section: Leggps1 Is Not a Typical Ja-or Sa-responsive Genementioning
confidence: 97%
See 2 more Smart Citations
“…Par茅 et al 1999;Bouwmeester et al 1999); (4) blends of HIPV not only emanate from the leaf under attack by the herbivore, but are also systemically induced in the plant (Turlings and Tumlinson 1992;Dicke 1994;Guerrieri et al 1999); (5) application of jasmonic acid (JA), a phytohormone, to wild-type plants or defence-signalling mutants leads to production of volatiles similar to HIPV (Hopke et al 1994;Ozawa et al 2000;Gols et al 2003;Thaler et al 2002;Van Poecke and Dicke 2003;Ament et al 2004); (6) herbivore-induced gene expression patterns in plants are similar to those mediated by jasmonates (e.g. Kant et al 2004;Ament et al 2004;Mercke et al 2004;Reymond et al 2004); (7) elicitors of HIPV synthesis in the plant have been found in the regurgitate/saliva of herbivores [N-(17-hydroxylinolenoyl)-L-glutamine or volicitin: Alborn et al 1997Alborn et al , 2000尾-glucosidase: Hopke et al 1994;Mattiacci et al 1995]s.…”
Section: Introductionmentioning
confidence: 99%